2019
DOI: 10.3389/fphar.2019.00138
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Practices, and Barriers of Malaysian Community Pharmacists Toward Provision of Weight Management Services

Abstract: In Malaysia, sharp increment in the prevalence of obesity over the last four decades has been documented. Community pharmacists (CPs) are strategically placed to tackle obesity by providing weight managements services (WMS) to general public. This study assessed the attitudes, practices and perceived barriers of Malaysian CPs to the provision of WMS. A cross-sectional, descriptive survey was conducted, and responses related to attitudes, practices and perceived barriers of CPs were collected using five-point L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…From patients' perspective, there is a lack of sensitivity about privacy requirements for discussions of sensitive issues such as obesity in community pharmacy (24). The issue of privacy was also raised in the findings of the previous quantitative study (8), in which it was one of the factors influencing the acceptability of community pharmacist-led WMS. In addition, the availability of a consultation room for discussion and consultation of all health issues to take place was one of the patient's considerations when choosing a pharmacy in the United Kingdom (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From patients' perspective, there is a lack of sensitivity about privacy requirements for discussions of sensitive issues such as obesity in community pharmacy (24). The issue of privacy was also raised in the findings of the previous quantitative study (8), in which it was one of the factors influencing the acceptability of community pharmacist-led WMS. In addition, the availability of a consultation room for discussion and consultation of all health issues to take place was one of the patient's considerations when choosing a pharmacy in the United Kingdom (25).…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this study support and further explain results from the previous quantitative study that aimed to assess the attitudes, practices, and perceived barriers of Malaysian community pharmacists in the delivery of WMS. In the previous quantitative study, while many of the community pharmacists were reported to actively provide WMS, they also perceived the presence of multiple barriers ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many potential barriers to effective obesity management in a hospital-based service for patients of older age. Moreover, there may be some inertia to referral of older patients from primary care or other specialist healthcare professionals in secondary care 16. Misconceptions about the utility and effectiveness of weight management in older patients may drive such attitudes.…”
mentioning
confidence: 99%
“…These also corroborated findings of researchers in Malaysia, who examined attitudes, practices and barriers to community pharmacists, led weight management. They found that collaboration and support counseling between community pharmacists and other health care practitioners resulted in better outcomes [19].…”
Section: Discussionmentioning
confidence: 99%